EFEKTIVITAS PENGGUNAAN BALIHO PADA PEMILUKADA - Akhwan Ali (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The main substance of this study was the effectiveness of billboard as a medium of political communication, in case ofthe mayor elections’ momentum and mayor of Pare Pare in 2013. Therefore, the problem formulation posed in this study were (i) why billboards were used as a medium of political communication in general elections of Mayor and Deputy Mayor of Pare Pare in 2013? (ii) whether the use of billboards was effective in increasing the candidates’ popularity and electability for Mayor and Deputy Mayor of Parepare, and (iii) what image was internalized by society to a billboard in the general election of Mayor and Deputy Mayor of Pare Pare? The purpose of this study was to describe and analyze billboard as a medium of political communication, effectiveness and political internalized image of the society as a voter. This study was using qualitative-comparative approach. Dataswere collected through unstructured interviews, documentation, and retrospective. The results of this study indicated that (i) the billboard was a practical political communication media. Messages and information contained therein can be directly communicated to the society that can be interpreted directly. In addition to their large size, billboards can be placed on public open spaces even to remote settlements. Thus the messages and information that can be socialized to the community directly to the bottom layer. (ii) the cost-effectiveness by use of billboards,instantaccess and information to the society has made billboards as the message conveyor can still be quite effective for the couple of candidates for mayor and deputy mayor in communicating their political goals in order to gain popularity and electability level in general elections of Mayor and Deputy Mayor of Pare Pare in 2013, and (iii) the public’stendency to assess the facts and political realities from candidate couplewas measured by the basic of knowledge and leadership experience against political promises and realization potential to promote development and people's lives.